Kompetensi Guru Sains Dalam Melaksanakan KTSP Di SMP/MTs Negeri Kota Ende - Maimunah H. Daud (Ekspektasi: Jurnal Pendidikan Ekonomi, 2016)
This study aims to reveal the competence of science teachers in implementing the Education Unit Level in SMP/MTs Ende Regency: the ability of teachers in terms of pedagogical and professional competence, pedagogic competence is limited to the ability in planning, implementation and evaluation, and professional competence is limited to the mastery of the material and educational background. This research was conducted eith survey approach. Subject were jujnior high school junior teachers, principals, and students at six school. The instrument used in this study was a questionnaire, interview, observation guidelines, documentation. Data were analyzed by using qualitative descriptive analysis. The man score of the competence of science teachers in SMP/MTs Ende Regency, at 84,5 pedagogical competence and the excellent category of professional competence 32,22 very good category.